Share repurchases and stock market reactions: Messages from the restaurant industry - Gim, Jaehee; Jang, SooCheong (Shawn) (International journal of hospitality management, 2020)
•There exits the long-lasting belief that share repurchase is a useful method for boosting undervalued stock prices.•The purpose of this study was to identify factors in the restaurant industry that could cause investors’ underreaction to share repurchases.•The results showed that growth opportunities, franchising and dividend payments have a negative impact on market reaction to share repurchases.•However, the negative impact of growth opportunities was found to be weaker for franchise restaurants than for non-franchise restaurants.•The results also revealed that spending excessive free cash flows on share repurchase causes markets’ underreaction to share repurchases. It is generally accepted that investors tend to react favorably to share repurchases. However, it is actually not uncommon for investors to underreact to some share repurchases. Recently, a number of restaurant firms have spent huge amounts of internal cash on share repurchases but little is known regarding the market’s underreaction to share repurchases in the restaurant industry. Hence, this study attempted to identify factors that could mitigate market reactions to share repurchases. Analyzing U.S. restaurant firms, this study revealed that growth opportunities, franchising, dividend payments, and spending excessive free cash flows on share repurchases negatively impacted market reactions. However, the negative impact of growth opportunities was weaker for franchise restaurants than for non-franchise restaurants. This study provides useful managerial information regarding the timing of and the amount that can be spent on restaurant firms’ share repurchases.